Comparison of Enoxaparin and Warfarin for Secondary Prevention of Cancer-Associated Stroke. (7th May 2015) - Jang, Hyemin; Lee, Jung Jae; Lee, Mi Ji; Ryoo, Sookyung; Yoon, Chang Hyo; Kim, Gyeong-Moon; Chung, Chin-Sang; Lee, Kwang Ho; Bang, Oh Young; Kim, Suk Jae
Abstract : Background . The aim of this study was to determine which anticoagulant is superior for secondary prevention of cancer-associated stroke, using changes in D-dimer levels as a biomarker for recurrent thromboembolic events. Methods . We conducted a retrospective, single center observational study including patients with cancer-associated stroke who were treated with either enoxaparin or warfarin. Blood samples for measuring the initial and follow-up D-dimer levels were collected at admission and a median of 8 days after admission, respectively. Multiple logistic regression analysis was conducted to evaluate the factors that influenced D-dimer levels after treatment. Results . Although the initial D-dimer levels did not differ between the two groups, the follow-up levels were dramatically decreased in patients treated with enoxaparin, while they did not change with use of warfarin (3.88 μ g/mL versus 17.42 μ g/mL, p = 0.026 ). On multiple logistic regression analysis, use of warfarin (OR 12.95; p = 0.001 ) and the presence of systemic metastasis (OR 18.73; p = 0.017 ) were independently associated with elevated D-dimer levels (≥10 μ g/mL) after treatment. Conclusion . In cancer-associated stroke patients, treatment with enoxaparin may be more effective than treatment with warfarin for lowering the D-dimer levels. Future prospective studies are warranted to show that enoxaparin is better than warfarin for secondary prevention in cancer-associated stroke.